Actual Power Consumption Values Of Alloy Steels – Experimental Results - Prof. G.L Datta., Chiluveru Parameshwar, Prof. R. Markandeya, (International Journal of Scientific Research and Management (IJSRM), 2015)
In this paper experimental heats were conducted for ascertaining actual energy required to produce one ton of liquid alloy steels. For this purpose 3.0T and 0.5 T Furnaces were selected in a foundry and experimental heats were conducted in a equi-uniform conditions. The furnaces were started from cold conditions, heated and metal was tapped till 3 rd heat. The charge consisted of scrap, foundry returns and additives on the basis of required chemistry of the client. The liquid metal was heated to the superheat and required quantity was tapped in to the ladles and poured in to the moulds. Energy readings were taken from the energy meter. Total liquid metal poured in the moulds is calculated.. Thus power consumption per one ton of liquid metal was arrived. As per the experiments 825 KWH energy was consumed for melting one Ton of Mn Steel , 886 KWH consumed for melting one ton of Carbon Steel. The power consumption was higher when the furnace was started from a Cold start( 1 st heat) and decreased by 100-120 KWH to the 2nd heat and further reduced by 30-50 to the third heat giving an indication that, if the process is continuous, there will be a saving of 100-150KWH per one ton of liquid metal for a 3.0 Ton Induction Furnace. The actual power consumption values are compared with the theoretical values. It is observed that the practical values are almost double the theoretical, giving a suggestion that the foundry under study has to apply efficient measure to save power.